SOSIALISASI MITIGASI BENCANA BERBASIS EDUKASI SAINS BAGI SISWA SEKOLAH DASAR MELALUI IMPLEMENTASI HASIL KUNJUNGAN ILMIAH KE BMKG - Mardova, Liyana; Putra, Febrianto; Sari, Rintan (Universitas Mataram, 2025)
Disaster preparedness is an important competency that must be instilled from an early age. Children, especially elementary school students, are a vulnerable group but have great potential to receive education about disaster mitigation. This activity aims to improve students' understanding of SDN 19 Martapura about the types of disasters and self-rescue measures through outreach. The activity implementation method uses an educational-participatory approach that actively involves students in every stage of learning. The activity stages begin with the preparation of materials and media, coordination with the school, interactive delivery of materials, demonstration of safety procedures, and implementation of evacuation simulations. The results of the activity showed a significant increase in students' knowledge and awareness of disaster mitigation. Before the outreach, only 15–20% of students knew disaster evacuation procedures, whereas after the activity, more than 85% of students were able to explain self-rescue steps correctly. Students were able to differentiate between natural and non-natural disasters, understand the